Supported Catalytically Active Supramolecular Hydrogels for Continuous Flow Chemistry. Issue 52 (6th November 2019) - Rodon Fores, Jennifer; Criado‐Gonzalez, Miryam; Chaumont, Alain; Carvalho, Alain; Blanck, Christian; Schmutz, Marc; Serra, Christophe A.; Boulmedais, F.; Schaaf, Pierre; Jierry, Loïc
Abstract: Inspired by biology, one current goal in supramolecular chemistry is to control the emergence of new functionalities arising from the self‐assembly of molecules. In particular, some peptides can self‐assemble and generate exceptionally catalytically active fibrous networks able to underpin hydrogels. Unfortunately, the mechanical fragility of these materials is incompatible with process developments, relaying this exciting field to academic curiosity. Here, we show that this drawback can be circumvented by enzyme‐assisted self‐assembly of peptides initiated at the walls of a supporting porous material. We applied this strategy to grow an esterase‐like catalytically active supramolecular hydrogel (CASH) in an open‐cell polymer foam, filling the whole interior space. Our supported CASH material is highly efficient towards inactivated esters and enables the kinetic resolution of racemates. This hybrid material is robust enough to be used in continuous flow reactors, and is reusable and stable over months. Abstract : CASH flow : Catalytically active supramolecular hydrogels (CASHs) generated from a porous polymer foam by an enzyme‐assisted self‐assembly strategy are ideal catalytic phases for continuous flow. A hydrogel prepared from an original bis‐phosphorylated heptapeptide enables highly efficient ester hydrolysis and kinetic resolution.